The influence of pole length on performance, O2 cost, and kinematics in double poling - Losnegard, T.; Myklebust, H.; Skattebo, Ø.; Stadheim, H. K.; Sandbakk, O.; Hallén, J. (International Journal of Sports Physiology and Performance, 2017)
Purpose: In the double-poling (DP) cross-country-skiing technique, propulsive forces are transferred solely through the poles. The aim of the current study was to investigate how pole length influences DP performance, O2 cost, and kinematics during treadmill roller skiing.